Blue Carbon Stock in Zostera marina Meadows in the Ría de Ferrol (NW Iberian Peninsula) - María del Carmen de la Cerda-Marín; Guillermo Díaz-Agras; Ramiro Rodríguez Tato; María Candás Romero; Marcos Pérez Señarís; Andrés de Solaun Eimil; Xosé Luis Otero; Xosé Luis Otero (Spanish Journal of Soil Science)
The increase in greenhouse gases (GHG) has been constant since the Industrial Revolution. For this reason, different international organizations have devoted special attention to GHG sinks such as terrestrial soils and ecosystems. However, the initially estimated balances did not include the carbon stock associated with ocean waters, coastal soils and sediments, known as blue carbon. Currently, blue carbon sinks are the subject of numerous studies due to the limited information available, especially on the Atlantic coast of the Iberian Peninsula. We studied the organic C stock present in soils and in Zostera marina biomass in the two main meadows in the Ría de Ferrol (O Baño and Castelo de San Felipe). The carbon stock associated with biomass was 0.37 Mg C ha−1, with 0.18 Mg C ha−1 corresponding to the epigeal portion and 0.19 Mg C ha−1 to the hypogeal portion. Soil carbon stock was much higher: 4.11 Mg C ha−1 at a depth of 5 cm and 82.14 Mg C ha−1 at a depth of 1 m. Together with carbon values in biomass, a stock of 82.5 Mg C ha−1 was obtained for the whole Ría de Ferrol. Z. marina accounted for 8.25% of total C in the Ría de Ferrol. These values were higher than those found in other regions. Isotope ratios (δ13C, δ15N) and C/N ratios indicated that the organic C stock in the O Baño soil may receive important organic matter inputs of terrestrial origin, while in San Felipe, it seems to have a marine origin.